Investigation Microwave Furnace Effects on Mechanical Properties and Fatigue Life of AA 7075-T73 with Dry and Acid Treatments - Aziz, Sadiq Jaffer; AL-Qisy, Ahmed Adnan; Salman, Rafeef Jumaa (Al-Khwarizmi Engineering Journal, 2019)
Microwave heating is caused by the ability of the materials to absorb microwave energy and convert it to heat. The aim of this study is to know the difference that will occur when heat treating the high strength aluminum alloys AA7075-T73 in a microwave furnace within different mediums (dry and acidic solution) at different times (30 and 60) minutes, on mechanical properties and fatigue life. The experimental results of microwave furnace heat energy showed that there were variations in the mechanical properties (ultimate stress, yielding stress, fatigue strength, fatigue life and hardness) with the variation in mediums and duration times when compared with samples without treatment. The ultimate stress, yielding stress and fatigue strength decreased for all states compared with standard values. With reference to fatigue life, the results showed that the increment in fatigue life occurred for test states of dry 60 minutes in a microwave furnace, which were only 25%. Moreover, the increment in hardness range was reached for test state of acid in 60 minutes which was about 7.3%, and 5 % for dry in 30 minutes and only 3%.